Inside the Noonan “universe”: Literature review on growth, GH/IGF axis and rhGH treatment: Facts and concerns - Stagi, Stefano; Ferrari, Vittorio; Ferrari, Marta; Priolo, Manuela; Tartaglia, Marco (Frontiers in Endocrinology, 2022)
Noonan syndrome (NS) is a disorder characterized by a typical facial gestalt, congenital heart defects, variable cognitive deficits, skeletal defects, and short stature. NS is caused by germline pathogenic variants in genes coding proteins with a role in the RAS/mitogen-activated protein kinase signaling pathway, and it is typically associated with substantial genetic and clinical complexity and variability. Short stature is a cardinal feature in NS, with evidence indicating that growth hormone (GH) deficiency, partial GH insensitivity, and altered response to insulin-like growth factor I (IGF-1) are contributing events for growth failure in these patients. Decreased IGF-I, together with low/normal responses to GH pharmacological provocation tests, indicating a variable presence of GH deficiency/resistance, in particular in subjects with pathogenic PTPN11 variants, are frequently reported. Nonetheless, short- and long-term studies have demonstrated a consistent and significant increase in height velocity (HV) in NS children and adolescents treated with recombinant human GH (rhGH). While the overall experience with rhGH treatment in NS patients with short stature is reassuring, it is difficult to systematically compare published data due to heterogeneous protocols, potential enrolment bias, the small size of cohorts in many studies, different cohort selection criteria and varying durations of therapy. Furthermore, in most studies, the genetic information is lacking. NS is associated with a higher risk of benign and malignant proliferative disorders and hypertrophic cardiomyopathy, and rhGH treatment may further increase risk in these patients, especially as dosages vary widely. Herein we provide an updated review of aspects related to growth, altered function of the GH/IGF axis and cell response to GH/IGF stimulation, rhGH treatment and its possible adverse events. Given the clinical variability and genetic heterogeneity of NS, treatment with rhGH should be personalized and a conservative approach with judicious surveillance is recommended. Depending on the genotype, an individualized follow-up and close monitoring during rhGH treatments, also focusing on screening for neoplasms, should be considered.